Fraxin modulates lipid metabolism as well as gut flora to avert NAFLD - Jing, Yang; Huicong, Dong; Xuanchi, Guo; Cao, Li; Huanhuan, Zhang; Yongze, Guo (Frontiers in Pharmacology, 2025)
BackgroundPublic healthcare systems are heavily burdened by non-alcoholic fatty liver disease (NAFLD), which is the leading “chronic liver disorder” around the globe. Fraxin, a natural compound extracted from Fraxini cortex in traditional Chinese medicine, exerts hepatoprotective effects. However, the mechanism by which fraxin alleviates NAFLD remains elusive. This research looks into fraxin’s therapeutic potential in NAFLD management using an integrated experimental and pharmacological strategy.MethodsFirst, network pharmacology was used to identify core therapeutic targets of fraxin for NAFLD. Second, we built protein-protein interaction (PPI) networks, followed by “Gene Ontology (GO)” along with “Kyoto Encyclopedia of Genes and Genomes (KEGG)” pathways. Molecular docking validated the interaction of fraxin with its predicted targets. To confirm fraxin’s therapeutic effect in vivo, we built a “methionine-choline-deficient” (MCD) diet-induced NAFLD mouse model. Comprehensive assessments included liver function tests, hepatic triglyceride content, inflammatory marker measurement, mRNA expression for key lipid metabolism enzymes through reverse transcription-polymerase chain reaction, fatty acid translocase/cluster of differentiation 36 (FAT/CD36) expression through Western blotting, and 16S ribosomal RNA sequencing to assess changes in metabolic dysfunction and the gut microbiota.ResultsNetwork pharmacology identified 34 potential fraxin targets in NAFLD. GO and KEGG analyses suggested that fraxin primarily treats NAFLD by modulating lipid metabolism and atherosclerosis-related signaling pathways. In vivo, fraxin significantly lowered liver index and visceral fat accumulation, reduced serum levels of “interleukin-6 (IL-6),” “aspartate aminotransferase,” “tumor necrosis factor-α (TNF-α)” and “alanine aminotransferase,” and decreased hepatic TG content. Furthermore, fraxin downregulated IL-6 and TNF-α expression and lowered the gene and protein levels of FAT/CD36, controlling key targets in signaling pathways related to lipid metabolism and atherosclerosis. Additionally, fraxin altered the gut microbial composition, reducing the Firmicutes/Bacteroidota ratio while increasing the abundance of Bacteroidota, Bacteroidia, Bacteroidales, Prevotellaceae, and Alloprevotella. Therefore, fraxin attenuated gut microbiota dysbiosis in mice caused by the MCD diet.ConclusionFraxin alleviates MCD diet-induced NAFLD by controlling lipid metabolism as well as restoring the homeostasis of gut microbiota.